EVALUATING PROSPECTIVE ELEMENTARY SCHOOL TEACHERS’ WRITTEN AND ORAL ARGUMENTS ON ECOLOGY - Okumuş, Seda; Öztürk, Bilge (International Online Journal of Education and Teaching, 2022)
This study aimed to evaluate prospective elementary school teachers’ skills in creating written and oral arguments about the ecology. The case study method, one of the qualitative research approaches, was used. The study group consisted of 38 prospective elementary school teachers studying in the third year of an elementary teaching undergraduate program. As data collection tools, an expressions table containing ecology topics was designed by the researchers to evaluate the written argument creation skills of the participants and audio recordings of discussions were used to determine their oral argument creation skills. Descriptive analysis was used to analyze the data obtained in these ways. According to the findings of this research, the written and oral arguments of these prospective elementary school teachers were concentrated at a moderate level, but their oral arguments were at a higher level than their written arguments. It can be concluded that oral classroom discussions are more effective than written activities in creating arguments about the ecology.